Biocontrol of fusarium ear rot of maize using Trichoderma species - Salleh, Suhaida (2013)
The present study conducted to screen the biocontrol agent of different species of Trichoderma against Fusarium ear rot (FER), which examined under in vitro and plant house conditions. Seventy-two isolates of Trichoderma were successfully isolated from rhizosphere of different crops. All isolates were identified into three species such as T. harzianum (51 isolates), T. koningii (20 isolates) and T. hamatum (1 isolate). Pathogenicity test of six isolates of Fusarium (B84c, C116c, C121c, P175c, P191c and P202c) to maize ear (variety Thailand Supersweet) and the symptoms development of FER were observed after seven days of pathogens inoculation. The results proved that F. proliferatum P202c and F. verticillioides C116c were pathogenic and caused FER. Both pathogens were challenged in dual culture test with 72 identified isolates of Trichoderma. Trichoderma harzianum T73s gave the highest percentage inhibition of 73.10% and 79.46% against F. proliferatum P202c and F. verticillioides C116c, respectively. The interaction appeared with the formation of clear zone between the pathogens and Trichoderma. Trichoderma harzianum T73s was further tested for its efficacy to suppress FER disease under plant house condition. The severity of FER was significantly reduced in the maize plants treated with T. harzianum T73s every week, immediately after planting (T1) with percentage of disease severity (DS) 10% and 8% against P202c and C116c, respectively. In contrast, the DS of positive control (C3) for P202c and C116c were 95% and 94%, respectively. The ears in T2 moderately suppressed FER with DS 38% and 34% against P202c and C116c, respectively. The ears for negative control that were inoculated with distilled water and uninoculated remained intact. The other treatments (T3 and T4) were unable to reduce the severity of FER disease. This study reported that T. harzianum T73s can be applied as a biocontrol agent and has a potential for further tests in the field and commercial scales.